Does teachers’ Interest Affect the Frequency of Teaching and Learning Outside the Classroom in Early Social Studies? - Jančič Hegediš, Polona (Revija za elementarno izobraževanje, 2025)
The article presents the findings of a study aimed at determining whether teachers’ personal interests and other factors influence the implementation of teaching and learning outside the classroom in early social studies within primary education. A convergent mixed-method research design was employed. The results indicate that, in practice, teaching and learning outside the classroom in early social studies is implemented less frequently than would be expected based on the didactic guidelines for early social studies instruction. Most teachers conduct such lessons only once a month or less. Teachers’ personal interests emerged as a significant factor influencing the frequency of teaching and learning outside the classroom.
Keywords: primary Education, Social Studies, Experiential Learning, Teaching and Learning outside the classroom, convergent mixed methods approach.